Antineutrophil Cytoplasmic Antibody Vasculitis after Coronary Artery Bypass Grafting - Dwight D. Harris; Sharif A. Sabe; Afshin Ehsan (Case Reports in Surgery)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis is a group of rare autoimmune disorders associated with the presence of ANCA autoantibodies. We present the first reported case of acute ANCA-associated vasculitis following coronary artery bypass grafting in a 74-year-old male presenting on postoperative day 13 with shortness of breath, orthopnea, and acute kidney injury. Renal biopsy ultimately showed focal necrotizing and crescentic glomerulonephritis, and the patient was successfully managed with corticosteroids and outpatient rituximab. This rare case highlights the importance of having an expanded differential for uncommon causes of cardiovascular disease and unexpected outcomes after coronary artery bypass grafting.